2007
DOI: 10.1061/(asce)1090-0241(2007)133:4(372)
|View full text |Cite
|
Sign up to set email alerts
|

Induced-Partial Saturation for Liquefaction Mitigation: Experimental Investigation

Abstract: The technical feasibility of a new liquefaction mitigation technique is investigated by introducing small amounts of gas/air into liquefaction-susceptible soils. To explore this potential beneficial effect, partially saturated sand specimens were prepared and tested under cyclic shear strain controlled tests. A special flexible liquefaction box was designed and manufactured that allowed preparation and testing of large loose sand specimens under applied simple shear. Partial saturation was induced in various s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
91
0
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(108 citation statements)
references
References 12 publications
3
91
0
6
Order By: Relevance
“…As experimental evidences of lowering liquefaction susceptibility induced by desaturation, Okamura and Teraoka (2005), Yegian et al (2007) and Takemura et al (2009) carried out 1g and centrifuge shaking table tests and showed that desaturation of foundation soil has signiˆcant eŠects to reduce generation of excess pore pressure and settlement of structures. Yoshimi et al (1989) have conducted cyclic torsional shear tests and concluded that a soil specimen shows threefold liquefaction resistance ratio as the degree of saturation decreases from fully-saturated to 70z.…”
Section: Introductionmentioning
confidence: 99%
“…As experimental evidences of lowering liquefaction susceptibility induced by desaturation, Okamura and Teraoka (2005), Yegian et al (2007) and Takemura et al (2009) carried out 1g and centrifuge shaking table tests and showed that desaturation of foundation soil has signiˆcant eŠects to reduce generation of excess pore pressure and settlement of structures. Yoshimi et al (1989) have conducted cyclic torsional shear tests and concluded that a soil specimen shows threefold liquefaction resistance ratio as the degree of saturation decreases from fully-saturated to 70z.…”
Section: Introductionmentioning
confidence: 99%
“…Small scale laboratory testing has shown the benefit of IPS as described in Yegian et al [1] and EsellerBayat et al [2], [3]. Most recently the benefit of IPS treatment was also observed and proven in large scale laminar box tests in NEES University of Buffalo facilities, these results were analyzed and presented by Nababan [4].…”
Section: Called "Induced Partial Saturation" (Ips)mentioning
confidence: 99%
“…Researches on finding effective and cost effective liquefaction mitigation techniques are still undergoing in many part of the world. One promising new mitigation technique which is innovative, practical, and cost effective was proposed by Yegian et al [1] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods about generating gas in pores of sands have been proposed. These including air injection (Okamura et al, 2006), water electrolysis (Yegian et al, 2007), drainage-recharge technique (Yegian et al, 2007), biogas . Biogas mainly is nitrogen gas produced by the microbial denitrification process.…”
Section: Introductionmentioning
confidence: 99%